Erich Przywara and Edith Stein: A Dissimilarity within Similarity: Their relationship in light of recent archival discoveries - Scerri, Carl (Modern theology, 2025)
Erich Przywara and Edith Stein were not only two of the leading Catholic intellectuals of the first half of the twentieth century, but also friends and confidants. This article explores the similarities and dissimilarities between their respective views on analogy. It also explains why so little of their correspondence has survived. Most importantly, this article presents a previously unknown poem co-authored by the two thinkers, which was discovered in the Przywara Archive. This is their only known cowritten document, and opens a window on the ideas, spiritualities, and personalities of both Przywara and Stein.